Lineage and hybridization effects on size potential in the Largemouth Bass complex. Issue 2 (16th March 2023) - Lutz‐Carrillo, Dijar J.; Schlechte, Warren; Norman, Jake; Bennett, Daniel L.
Abstract: Objective: Introductions of Florida Bass Micropterus floridanus (FB) to Texas resulted in prevalent hybridization with Largemouth Bass M. salmoides (LB) and the creation of hybrid‐dominated fisheries. However, little was known about the size potential of these hybrids relative to each other or relative to the parental taxa. Methods: Sampling of these taxa and their hybrids in Texas (populations = 166; n = 8685) and genotyping at taxon‐diagnostic microsatellite loci facilitated comparisons of allele and genotype frequencies among weight‐classes. Result: Results indicated that per capita, fish that were 100% FB were much more likely to attain moderate (≥3.63‐kg) to large (≥5.9‐kg) size than any other genotype in the species complex. Among hybrids, F1 genotypes were likely to reach moderate to large sizes at rates similar to hybrids with high levels of FB alleles; otherwise, the likelihood of reaching large size scaled positively with levels of FB alleles. Hybrids with <50% FB alleles and fish that were 100% LB were almost non‐existent in the moderate and large size‐classes. A case study in Lake Fork ( n = 510) provided similar results, although F1 genotypes were more likely to reach large size than any other hybrid. Conclusion: These findings provide evidence for positive size‐related heterosis in the F1 generation and suggest that absent heterotic effects, size potential in hybrids is driven by many small additive‐effect loci. Abstract : Impact Statement Genetic analyses indicated positive size‐related heterosis for F1 hybrids in the Largemouth Bass complex, and size potential scaled positively with levels of Florida Bass alleles, but non‐introgressed Florida Bass were still much more likely to reach large size.